On small huntsman spiders (Araneae, Philodromidae) occurring in Guizhou and Hubei provinces, China - Jianshuang Zhang; Chengwen Zhang; Yang Zhong (ZooKeys)
Spiders of the family Philodromidae Thorell, 1869 from Guizhou and Hubei provinces, China are studied. A total of three genera and seven species are reported and illustrated, comprising Sinodromus lanyue sp. nov. (newly recorded genus for Hubei), and all known species from both provinces: Philodromus auricomus L. Koch, 1878, P. guiyang Long & Yu, 2022, P. subaureolus Bösenberg & Strand, 1906, P. paiki Jang, Lee, Yoo & Kim, 2024 (the previously records of P. spinitarsis Simon, 1895 from Guizhou and Hubei are presumed to be misidentifications, and should belong to P. paiki), P. rufus Walckenaer, 1826 (new record for Hubei) and Tibellus japonicus Efimik, 1999 (new record for Hubei). Detailed descriptions, diagnoses, and illustrations of S. lanyue sp. nov. and P. guiyang are given, and the male of P. guiyang is diagnosed and described in English for the first time. The other five species are also re-illustrated. Their DNA barcodes were obtained for species delimitation, matching of sexes and future use.